2020
DOI: 10.47440/jafe.2020.1301
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood improvement of farmers through cattle fattening of Mymensingh District: A socio-economic study

Abstract: The experiment was conducted to investigate the livelihood improvement of farmers through cattle fattening in selected areas (Mymensingh Sadar and Fulbaria Upazilla) in Mymensingh district of Bangladesh through field survey. Total of 30 respondents were randomly selected from the three villages. Each village consists of 10 respondents. Data were collected from randomly selected 30 farmers who were involved in small scale cattle fattening through personal interviews. The selected characteristics were the socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
3
0
0
Order By: Relevance
“…The present study indicates that most of the respondents (53.12 %) were a middle-aged group which is similar to a study from Karim (2020) where highest proportion (56.7%) of farmers was reported in the middle-aged. The above result is also in agreement with the findings of Shahjahan and Bhuiyan (2016), Sarker et al (2017), and Girish et al (2020).…”
Section: Socio-economic Profile Of the Farmersupporting
confidence: 91%
See 2 more Smart Citations
“…The present study indicates that most of the respondents (53.12 %) were a middle-aged group which is similar to a study from Karim (2020) where highest proportion (56.7%) of farmers was reported in the middle-aged. The above result is also in agreement with the findings of Shahjahan and Bhuiyan (2016), Sarker et al (2017), and Girish et al (2020).…”
Section: Socio-economic Profile Of the Farmersupporting
confidence: 91%
“…In this study it was found that the majority of the respondents (49.16%) were having a medium family size. The findings of Karim et al (2020) and Girish et al (2020) supported the present results whereas the findings of Rahman et al (2012) were contradictory. It was observed that farmers were involved in various occupations such as in agriculture, business, and services.…”
Section: Socio-economic Profile Of the Farmersupporting
confidence: 81%
See 1 more Smart Citation